Business cycle – growth nexus: a review - Škare, Marinko; Tomić, Daniel (Technological and Economic Development of Economy, 2015)
Frequent reversals in business cycles pose the question whether country can achieve macroeconomic stability and/or economic growth by coordinating its economic policies. Thus, what is the role of economic policy within the short/long run in amplifying or dampening shocks? Business cycle – economic growth relationship is rather ambiguous and has, thus, attracted controversy. In this sense the (dis)belief that there indeed exists a relationship between the economic growth and business cycle, and their long-run convergence brings us to three important hypotheses that: (1) the evaluation of cycle-growth bond is inconclusive, (2) empirical testing of cycle synchronization is exaggerated and (3) the hypothesis of coupling/decoupling is ambiguous and can be misleading. Economic growth is a complex process and cannot be attributed to a single factor of observance hence this essay is just a tool of theoretical reasoning with firm grip on empirical circumstances that lead us to consider some issues that dwell the “growth economists” these days. Our study suggests a conclusion that discussions on the cycle-growth nexus are far from over, revealing us some remarkable confrontations within empirical domain.